Dynamic model and control strategies of battery-supercapacitor hybrid power sources for electric vehicles: a review - Al Tahtawi, Adnan Rafi; Rohman, Arief Syaichu; Rusmin, Pranoto Hidaya; Rizqiawan, Arwindra (Institute of Advanced Engineering and Science, 2025)
The addition of a supercapacitor to electric vehicles is considered beneficial for extending battery lifetime. Due to its higher power density compared to the battery, a supercapacitor can efficiently handle sudden high-current demands. However, to achieve energy efficiency, a specific control strategy is required for this battery-supercapacitor (Batt-SC) hybrid power source (HPS). This paper reviews the dynamic model of the Batt-SC as HPS for electric vehicles and explores its various control strategies in order to achieve energy efficiency. A high-fidelity model, a control-oriented model, and an integrated dynamic model are presented. Various control strategies are then discussed, including high-level control, low-level control, and DC bus voltage regulation. This paper also identifies several key research opportunities, such as developing an integrated dynamic model of a hybrid Batt-SC electric vehicle, combining high-level and low-level control into a unified control strategy, and designing an optimal-adaptive controller that can minimize a certain performance index by considering nonlinearity factors.